Team Collaboration and Productivity: Experiences of agile, hybrid, and traditional teams with remote work during the COVID-19 pandemic - Martin Krzywdzinski (Weizenbaum Institute for the Networked Society - The German Internet Institute, 2022)
The shift to remote work poses particular challenges for teamwork. It makes spontaneous and informal communication more difficult and may weaken social relations in teams. This study based on an online survey of 1,516 individuals who worked from home during the COVID-19 pandemic examines the functioning of teamwork in remote-work contexts and attempts to answer the following questions: (1) What organizational and technical working conditions influence working from home during the COVID-19 pandemic? (2) How did collaboration in different forms of teamwork evolve under working-from-home conditions during the COVID-19 pandemic? (3) What effects of working from home during the COVID-19 pandemic can be observed in terms of teamwork productivity? Overall, the study reveals quite surprising differences between different forms of team organization. The quality of team collaboration and team productivity slightly increased in agile teams, even in a situation where at least some members of the team were working from home. In contrast, respondents working in traditional teams reported slightly negative effects of working from home on teamwork quality and team productivity.
Additional information: This work has been funded by the Federal Ministry of Education and Research of Germany (BMBF) (grant no.: 16DII121, 16DII122, 16DII123, 16DII124, 16DII125, 16DII126, 16DII127, 16DII128 - "Deutsches Internet-Institut").
Keywords: 330; Telearbeit; Teamarbeit; Produktivität; Epidemie; soziale Beziehungen; Kommunikationsbedingung; Interaktion